PENGENALAN KEARIFAN LOKAL KALIMANTAN SELATAN UNTUK SISWA SD MELALUI BOOKLET SEBAGAI SUMBER BELAJAR DI SD IT ROBBANI BANJARBARU - Lestari, Nana Citrawati; Mayasari, Ria; Wulandari, Arina; Arifin, Muhammad (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2024)
The implementation of the Merdeka Curriculum in elementary schools can be done by introducing local wisdom culture. The learning resource used in this PKM activity is a booklet based on the local wisdom of South Kalimantan. The use of a local wisdom-based booklet can help teachers in implementing learning activities in schools. The selection of a booklet is because of its smaller size than a book and its concise content. In addition, visualizing the local wisdom booklet that the PKM team uses is designed to be more dominant with pictures, so its appearance will be more attractive. The purpose of this design is for the booklet to be more attractive to students and easier to understand. This community service activity is carried out in several forms of activities, namely observation, booklet distribution, socialization, discussion, and asking for feedback from respondents. The introduction of South Kalimantan's local wisdom to elementary school students through booklets as a learning source at IT Robbani Banjarbaru Primary School can be carried out well and effectively. Participants also responded positively to the implementation of the activity and the booklet presented. In other words, this activity has achieved the intended objectives.